Highly enantioselective Pd-catalyzed synthesis of P-stereogenic supramolecular phosphines, self-assembly, and implication - Koshti, Vijay S.; Mote, Nilesh R.; Gonnade, Rajesh G.; Chikkali, Samir H. (Organometallics, 2015)
Metal-catalyzed asymmetric addition of a secondary phosphine to an aryl halide is one of the most efficient and reliable approaches for the construction of enantiopure carbon phosphorus bonds. An isolated Pd(II) complex (5) catalyzes the carbon phosphorus coupling reaction between tolylphenylphosphine (la) and 3-iodophenylurea (2b), which proceeds with an unprecedented enantiomeric excess (ee) of 97%. The generality of the strategy has been demonstrated by preparing a small library of a new class of P-stereogenic phosphines with an in-built hydrogen bonding motif for the first time. The P-stereogenic phosphines self-assemble on a metal template via deliberately installed hydrogen-bonding motifs and mimic the bidentate ligand coordination. Interestingly, when it was employed in asymmetric hydrogenation, the supramolecular phosphine {1-(3-(phenyl(o-toly)phosphanyl)pheny)ureal} (6b) produced the corresponding hydrogenated product with the highest enantiomeric excess of 99% along with excellent conversion, demonstrating the potential of these enantioenriched P-chirogenic supramolecular phosphines in asymmetric catalysis.

Impact of modular substitution on crystal packing: the tale of two ureas - Koshti, Vijay S.; Thorat, Shridhar H.; Gote, Ravindra P.; Chikkali, Samir H.; Gonnade, Rajesh G. (CrystEngComm, 2016)

H-Bonding assisted self-assembly of anionic and neutral ligand on metal: a comprehensive strategy to mimic ditopic ligands in olefin polymerization - Mote, Nilesh R.; Patel, Ketan; Shinde, Dinesh R.; Gaikwad, Shahaji R.; Koshti, Vijay S.; Gonnade, Rajesh G.; Chikkali, Samir H. (Inorganic Chemistry, 2017)
Self-assembly of two neutral ligands on a metal to mimic bidentate ligand coordination has been frequently encountered in the recent past, but self-assembly of an anionic ligand on a metal template alongside a neutral ligand remains an elusive target. Such a self-assembly is hampered by additional complexity, wherein a highly negatively charged anion can form intermolecular hydrogen bonding with the supramolecular motif, leaving no scope for self-assembly with neutral ligand. Presented here is the self-association of anionic ligand 3-ureidobenzoic acid (2a) and neutral ligand 1-(3-(diphenylphosphanyl)phenyl)urea (1a) on a metal template to yield metal complex [{COOC6H4-NH(CO)NH2}{Ph2PC6H4NH(CO)NH2}PdMeDMSO] (4a). The identity of 4a was established by NMR and mass spectroscopy. Along the same lines, 3-(3-phenylureido)benzoic acid (2b) and 1-(3-(diphenylphosphanyl)phenyl)-3-phenylurea (1b) self-assemble on a metal template to produce palladium complex [{COOC6H4NH(CO)NHPh}{Ph2PC6H4NH(CO)NHPh}PdMePy] (5c). The existence of 5c was confirmed by Job plot, 1-2D NMR spectroscopy, deuterium labeling, IR spectroscopy, UV-vis spectroscopy, model complex synthesis, and DFT calculations. These solution and gas phase investigations authenticated the presence of intramolecular hydrogen bonding between hydrogen's of 1b and carbonyl oxygen of 2b. The generality of the supramolecular approach has been validated by preparing six complexes from four monodentate ligands, and their synthetic utility was demonstrated in ethylene polymerization. Complex 4a was found to be the most active, leading to the production of highly branched polyethylene with a molecular weight of 55700 g/mol and melting temperature of 112 degrees C.

Reactivity of difunctional polar monomers and ethylene copolymerization: a comprehensive account - Gaikwad, Shahaji R.; Deshmukh, Satej S.; Koshti, Vijay S.; Poddar, Suparna; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Chikkali, Samir H. (Macromolecules, 2017)
A comprehensive picture of insertion of 1,1-disubstituted difunctional olefins, their ability to double the functional group density at the same level of incorporation as that of monofunctional olefin, and copolymerization with ethylene has been demonstrated. Exposure of a palladium complex [P boolean AND OPdMe(L)] (P boolean AND O = kappa(2)-P,O-Ar2PC6H4SO2O with Ar = 2-MeOC6H4.; L = C2H6OS) to methyl 2-acetamidoacrylate (MAAA) revealed slight preference for 1,2-insertion over 2,1-insertion (1.0:0.7). In contrast, insertion of electron-deficient 2-(trifluoromethyl)acrylic acid (TFMAA) unveiled selective 2,1-insertion {via [(P boolean AND O)PdC5H6F3O2] (11)1. The unstable intermediate 11 undergoes beta-hydride and beta-fluoride elimination to produce subsequent insertion and elimination products. The identity of elimination products (E/Z)-2-trifluoromethyl)but-2-enoic acid [17(E/Z)] and 2-(difluoromethylene)butanoic acid (13) was fully established by 1-2D NMR spectroscopy. These insertion experiments, taken together with insertion rates, suggest that MAAA and TFMAA. are amenable to insertion. Polymerization of ethylene with MAAA, TFMAA, acetamidoacrylic acid, 2-bromoacrylic acid, dimethyl allylmalonate, and allylmalonic acid was catalyzed by [P boolean AND OPdMe(L)] (L = C2H3N) (S.ACN), and the highest incorporation of 11.8% was observed for dimethyl allylmalonate (DMAM). The changes in the surface properties of the copolymers after incorporation of difunctional olefins were evaluated by measuring the water contact angle. Copolymer with highest (11.8% of DMAM) incorporation revealed a reduced water contact angle of 76 degrees. These findings demonstrate that 1,1-disubstituted difunctional olefins are amenable to polymerization, and incorporation of difunctional olefins In polyethylene backbone leads to the production of relatively hydrophilic polyethylene copolymers.

Self-assembly of P-chiral supramolecular phosphines on rhodium and direct evidence for Rh-catalyst-substrate interactions - Koshti, Vijay S.; Sen, Anirban; Shinde, Dinesh; Chikkali, Samir H. (Dalton Transactions, 2017)
Supramolecular phosphine-derived catalysts are known to provide high enantioselectivity in asymmetric transformations such as hydrogenation, but direct evidence unravelling the role of secondary interactions is largely missing. As a representative case study, the role of hydrogen bonding in asymmetric hydrogenation catalysed by p-chiral supramolecular phosphines is investigated. To establish the nature of hydrogen bonding in the self-assembled Rh-complex, NMR experiments were performed at different concentrations and temperatures. It was found that with increasing concentration of 1-(3-(phenyl(o-tolyl)phosphanyl) phenyl) urea ligand (L1), the NH and NH2 peaks shift downfield. This indicated the presence of intermolecular hydrogen bonding in L1. This observation was further supported by variable temperature NMR experiments wherein, with decreasing temperature, the NH and NH2 resonances of L1 shifted downfield. The downfield shift once again suggests the existence of intermolecular hydrogen bonding in L1. In contrast, the chemical shift of NH and NH2 signals did not significantly change with increasing concentration of the self-assembled Rh-complex (C1). This observation suggested the existence of intramolecular hydrogen bonding in the self-assembled complex. The concentration experiment was further corroborated by variable temperature NMR experiments. No change in the chemical shift of NH2 resonance could be detected with decreasing temperature, which corroborates the existence of intramolecular hydrogen bonding in C1. In a stoichiometric experiment, C1 was treated with hydrogenation substrate N-acetyldehydrophenylalanine (S2) and the proton NMR was recorded. The NH2 protons of the selfassembled Rh-complex were found to shift downfield, as compared to untreated parent C1. These observations indicated that there is a hydrogen bonding interaction between the Rh-complex and the substrate. To further attest this hypothesis, NH and NH2 groups were exchanged with ND and ND2 groups, respectively, and a self-assembled Rh-complex was prepared using the deuterated supramolecular phosphine ligand L1.D. When the deuterated Rh-complex (C1.D) was treated with substrate S2, the ND and ND2 resonances were found to shift downfield. Thus, the labelling experiment further authenticated the existence of catalyst-substrate interactions. The presence of this catalyst-substrate interaction could be one of the parameters that leads to high enantiomeric excess in the asymmetric hydrogenation reaction of S2.

Accelerated and enantioselective synthesis of a library of p-stereogenic urea phosphines - Koshti, Vijay S.; Gote, Ravindra P.; Chikkali, Samir H. (European Journal Of Organic Chemistry, 2018)
Chiral phosphorus ligands play a central role in majority of the asymmetric transformations. However, access to chiral phosphorus ligands is limited due to their challenging synthesis. Reported here is a highly efficient and accelerated catalytic asymmetric synthesis of P-stereogenic urea containing phosphines leading to a small library of 18 chiral phosphorus compounds. Characteristic two doublets in a P-31 NMR spectrum, spectroscopic and analytical evidences authenticated the formation of [Pd-{(S,S) Me-FerroLANE}(m-phenylurea)(I)] complex. Indeed, [Pd-{(S,S) Me-FerroLANE}(m-phenylurea)(I)] was found to catalyze the C-P coupling reaction and quantitative conversion was observed within 18 hours. Under optimized conditions, iodophenyl urea's (2a-2j) were treated with secondary phosphines (1a-1c) in presence of [Pd-{(S,S) Me-FerroLANE}(m-phenylurea)(I)] to obtain P-stereogenic urea phosphines 5a-5r. The identity of these urea derived phosphines was unambiguously ascertained using a combination of spectroscopic and analytical methods. The catalyst tolerated various functional groups and yielded corresponding urea containing phosphines with an enantiomeric excess in the range of 15-62 %.

Noncovalent interactions in hydrogenation and hydroformylation - Koshti, Vijay S.; Chikkali, Samir H. (Noncovalent Interactions in Catalysis, 2019)
This chapter summarizes the fundamentals of hydrogenation and hydroformylation reactions. An overview of state-of-the-art developments is presented to set the context. Subsequently, the significance of noncovalent interactions in these reactions is discussed in detail. Hydrogen bonding has been one of the leading noncovalent interactions that has been very frequently used in catalysis, including hydrogenation and hydroformylation reactions. Recent examples from the literature are presented to illustrate the role of hydrogen bonding in hydrogenation and hydroformylation. The impact of hydrogen bonding on catalyst development through self-assembly and the role of hydrogen bonding in directing a substrate to achieve high enantiomeric excess are discussed.